Argatroban more effectively inhibits the thrombin activity in synovial fluid than naturally occurring thrombin inhibitors - Asanuma, K; Yoshikawa, T; Yoshida, K; Okamoto, T; Asanuma, Y; Hayashi, T; Akita, N; Oi, T; Nishimura, A; Hasegawa, M; Sudo, A (Cellular and Molecular Biology, 2016)
The purpose of this study was to clarify the precise effect of argatroban on the inhibition of cytokine secretion induced by thrombin on synovial cells. The efficiency of thrombin inactivation by thrombin inhibitors was evaluated in human synovial fluids (SFs). In SFs from 13 osteoarthritis (OA) and 11 rheumatoid arthritis (RA) patients, thrombin, Factor Xa (FXa), plasmin activity, IL-6, MMP-3, VEGF, and D-dimer concentrations were measured. Tissue factor (TF) activity or IL-6, MMP-3, and VEGF secretion of human synovial cells with or without thrombin and argatroban were measured. The efficiency of thrombin inactivation in SFs was compared for thrombin inhibitors: argatroban, antithrombin III (ATIII), or heparin cofactor II (HCII). In SFs, thrombin, FXa, plasmin, D-dimer, IL-6, and MMP-3 were significantly higher in RA than in OA. In synovial cell experiments, TNF-alpha and thrombin enhanced TF activity on the cell surface, and IL-6, MMP-3, and VEGF secretion were enhanced by thrombin. Increased TF activity, and IL-6, MMP-3, and VEGF secretion induced by thrombin were inhibited by argatroban. In SFs, argatroban inactivated thrombin more effectively than ATIII or HCII. Since thrombin plays an important role in the disease activity of OA and RA, it is a potential therapeutic molecular target. Argatroban was the most effective anticoagulant to inhibit thrombin activity in SF. Intra-articular injection is ideal administration because it can deliver high dose of argatroban without high risk of systematic complication.